The treatment of nephrogenic systemic fibrosis with therapeutic plasma exchange. Issue 4 (21st February 2013) - Poisson, Jessica L.; Low, Aaron; Park, Yara A.
<x xml:space="preserve">Abstract</x> Background: Nephrogenic systemic fibrosis (NSF), also known as nephrogenic sclerosing dermopathy (NSD), is a rare progressive fibrosing disease associated with gadolinium based dyes in patients with renal disease. The exact pathophysiology is not well understood. Accepted treatments include corticosteroids, immune modulators, PUVA, rituximab and extracorporeal photopheresis (ECP). Apheresis is utilized when symptoms continue to progress. However, the paucity of centers offering ECP can be inhibitory to care. Small case reports have been published illustrating moderate treatment success with therapeutic plasma exchange (TPE). Methods: Chart review found two patients; both were African‐American women with systemic lupus erythematosus (SLE), status post renal transplant, who had biopsy documented NSF. The patients were still symptomatic, despite maximal medical management, so they underwent TPE series for symptom management. Medical therapy with immune modulators was continued in conjunction to TPE. Response to treatment was evaluated using subjective reporting to the primary care team. Results: The patients reported significant improvements in subjective pain levels after TPE. Patient 1 reported decreased skin and contracture pain after the 3rd treatment, with similar results for a second series 6 months later. Patient 2 reported drastic improvement in pain symptoms and rarely required pain medication during hospital course. No adverse reactions occurred during treatment. Conclusions: TPE is a therapy option for patients with NSF without access to ECP. TPE was well‐tolerated, easily assessable, and effective; however the etiology of the improvement following TPE is unknown. Larger studies will help further determine the efficacy of TPE for NSF. J. Clin. Apheresis 28:317–320, 2013. © 2013 Wiley Periodicals, Inc.